On the limit polynomial for a solution of an elliptic equation of the fourth order with constant coefficients - Foiad, Sobhi Obaid (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We show that a solution of the Dirichlet problem for an elliptic equation of the fourth order with constant coefficients, whose right-hand side is periodic in all variables except one and exponentially decreases, converges at infinity to a certain polynomial of the first degree in the nonperiodic variable. Coefficients of this polynomial are determined.